Loss of E-cadherin Expression Stratifies Aggressive versus Non-Aggressive Papillary Thyroid Carcinoma - Dwi Yanti Fioni Putri; Yenita; Aswiyanti Asri; Tofrizal; Rony Rustam; Husna Yetti (HM Publisher, 2026)
Background: Papillary thyroid carcinoma (PTC) is generally indolent, yet specific histological subtypes defined by the World Health Organization (WHO) are linked to aggressive behavior and poor prognosis. The loss of the cell-adhesion protein E-cadherin is a hallmark of the epithelial-to-mesenchymal transition (EMT), a process implicated in tumor aggression. However, its role in stratifying PTC subtypes versus its correlation with tumor stage remains a significant controversy in the literature. This study aimed to disentangle these two parameters by clarifying the relationship between E-cadherin expression and both histological phenotype and tumor stage. Methods: This was an observational, cross-sectional pilot study on 40 randomly selected, formalin-fixed, paraffin-embedded (FFPE) PTC cases from a 2024 cohort (N=74) at a tertiary hospital in Indonesia. All cases were re-evaluated and classified according to the WHO 5th Edition (2022) criteria as non-aggressive (n=34) or aggressive (n=6). E-cadherin expression was assessed by immunohistochemistry (IHC) using a standardized semi-quantitative scoring system (product of intensity and proportion) adapted from previous studies, with inter-rater reliability assessed (Cohen’s Kappa = 0.88). Scores were dichotomized as 'High' (n=25) or 'Low' (n=15). The association between E-cadherin expression and both histological subtype and AJCC 8th Edition tumor stage (Early: I/II [n=32] vs. Advanced: III/IV [n=8]) was analyzed using Fisher's Exact Test, with Odds Ratios (OR) and 95% Confidence Intervals (CI) calculated. Results: High E-cadherin expression was observed in 62.5% of cases. A statistically significant and strong association was found between E-cadherin expression and histological subtype (p=0.021; OR 12.0; 95% CI 1.2–118.9). Low E-cadherin expression was present in 83.3% (5 of 6) of aggressive-subtype tumors, versus only 29.4% (10 of 34) of non-aggressive subtypes. In contrast, no significant correlation was found between E-cadherin expression and advanced tumor stage (p=0.126; OR 3.67; 95% CI 0.7–18.6). Conclusion: Loss of E-cadherin expression is a significant biomarker associated with high-risk, aggressive histological phenotypes in PTC. Its lack of correlation with tumor stage, confirmed by an uncertain OR, suggests E-cadherin's role is indicative of an inherent tumor biological phenotype (aggressiveness) rather than a linear marker of tumor progression (stage). This dichotomy, likely reflecting EMT/MET plasticity, positions E-cadherin IHC as a powerful ancillary tool for pathological risk stratification.